THE VARIATIONS USED OF GELLING AGENT MATERIAL TOWARD COCOA (Theobroma cacao) PULP TRADITIONAL CANDY CHARACTERISTICS - Hesti Nur’aini (BPFP Faperta UNIB, 2013)
Research has been conducted in order to determine the effect of gelatin and agarose quality of the physical and chemical characteristics of traditional cocoa pulp candy and to determine the type of gelling egent affecting traditional cocoa pulp candy characteristics. The study comprised three steps, namely preparation of basic materials (cocoa pulp preparation), the processing stage traditional candy made from cacao pulp with a variety of cacao pulp concentration (5%, 10% and 15%) and type of gelling agent namely gelatin and agar-agar, analysis phase includes analysis of water content, texture (hardness), and sensory testing using trained panelists. The results showed traditional sweets of cocoa pulp texture value 10:00 - 12:50 mm/g, a water content of between 47.09-54.17%. Based on the analysis of the sensory test, no significant differences in the parameters of the appearance and taste of traditional candy of cocoa pulp, while the springy parameter, panelists judged that the most traditional candy of cocoa pulp is chewiest candy with “agar” as gelling agent treatment order and 10% cocoa pulp.